High-efficient production of biobutanol by a novel Clostridium sp. strain WST with uncontrolled pH strategy. (May 2018) - Shanmugam, Sabarathinam; Sun, Chongran; Zeng, Xiaoming; Wu, Yi-Rui
Highlights: A newly isolated Clostridium sp. WST with efficient butanol-producing capability was identified. The biobutanol production of 16.62 g/L can be archived by using 30 g/L of glucose as the substrate. The biobutanol yield of 0.54 g/g was much higher than those from the reported Clostridial strains. Neglectable amount of ethanol was detected during the fermentation by strain WST. The self-regulatory system enables this strain to be without the requirement of pH control. Abstract: A novel Clostridium sp. strain WST isolated from mangrove sediments demonstrated its unique characteristics of producing high titer of biobutanol from low concentration of substrates via anaerobic fermentation. The strain is able to convert glucose and galactose to high amount of biobutanol up to 16.62 and 12.11 g/L, respectively, and the yields of 0.54 and 0.55 g/g were determined to be much higher than those from the previous reports on Clostridial batch fermentation. Moreover, the inherent strong regulatory system of strain WST also prompts itself to perform the fermentation process without any requirement of pH control. In addition to tolerance of high butanol concentration and negligible production of by-products (e.g., ethanol or acids), this strain has immense potential for the sustainable industry-scale production of biobutanol.